How Gender and Race Stereotypes Impact the Advancement of Scholars in STEM: Professors’ Biased Evaluations of Physics and Biology Post-Doctoral Candidates - Eaton, Asia A.; Saunders, Jessica F.; Jacobson, Ryan K.; West, Keon (Sex roles, 2020)
The current study examines how intersecting stereotypes about gender and race influence faculty perceptions of post-doctoral candidates in STEM fields in the United States. Using a fully-crossed, between-subjects experimental design, biology and physics professors ( n = 251) from eight large, public, U.S. research universities were asked to read one of eight identical curriculum vitae (CVs) depicting a hypothetical doctoral graduate applying for a post-doctoral position in their field, and rate them for competence, hireability, and likeability. The candidate’s name on the CV was used to manipulate race (Asian, Black, Latinx, and White) and gender (female or male), with all other aspects of the CV held constant across conditions. Faculty in physics exhibited a gender bias favoring the male candidates as more competent and more hirable than the otherwise identical female candidates. Further, physics faculty rated Asian and White candidates as more competent and hirable than Black and Latinx candidates, while those in biology rated Asian candidates as more competent and hirable than Black candidates, and as more hireable than Latinx candidates. An interaction between candidate gender and race emerged for those in physics, whereby Black women and Latinx women and men candidates were rated the lowest in hireability compared to all others. Women were rated more likeable than men candidates across departments. Our results highlight how understanding the underrepresentation of women and racial minorities in STEM requires examining both racial and gender biases as well as how they intersect.